Acoustic Monitoring of Night-Time Respiratory Symptoms in 14 Patients with Exacerbated COPD Over a 3- Week Period - Boeselt T; Kroenig J; Lueders TS; Koehler N; Beutel B; Hildebrandt O; Koehler U; Conradt R (International Journal of COPD, 2022)
Tobias Boeselt,1 Johannes Kroenig,1 Theresa-Sophie Lueders,1 Niklas Koehler,2 Bjoern Beutel,1 Olaf Hildebrandt,1 Ulrich Koehler,1 Regina Conradt1 1Department of Internal Medicine, Division of Pneumology, Intensive Care and Sleep Medicine, Philipps-University Marburg, Marburg, Germany; 2Thora Tech GmbH, Clinical Research Department, Gießen, GermanyCorrespondence: Tobias Boeselt, Department of Internal Medicine, Division of Pneumology, Intensive Care and Sleep Medicine, Philipps-University Marburg, Baldingerstrasse 1, Marburg, 35033, Germany, Email tobias.boeselt@uni-marburg.deIntroduction: In clinical practice, wheezing and coughing represent a worsening of the respiratory situation of COPD patients and should be monitored long-term during and after an Acute Exacerbation of COPD (AECOPD) to observe the therapy. We investigated if overnight monitoring of wheezing and coughing is feasible during AECOPD and whether automatic long - term monitoring enables an objective assessment during and after an AECOPD.Methods: In 14 patients (age: 56– 80 years) with pre-existing COPD (stages B-D) nighttime wheezing and coughing events were monitored for a period of three weeks. The portable LEOSound® monitor recorded three nights into AECOPD (nights 1, 3 and 6) during the hospital stay, and the 20th night post- AECOPD ambulatory. Before each recording the subjective symptom severity was assessed by a COPD Assessment Test (CAT) and a Modified British Medical Research Council (MMRC) dyspnoea index questionnaire.Results: In all 14 patients, lung sounds were recorded in good quality during each of the 4 recording nights. Wheezing ranged between 5% and 90% (79 − 539.5 minutes) of the recording time on the first night. All patients showed some coughs, in four patients coughing was particularly pronounced and largely receding over the total investigation period. As group, the percentages of wheezing and the number of coughs did not show significant differences between the four recording times. The CAT scores (p< 0.001) declined over the course of investigation period, suggesting a subjective improvement of symptoms.Conclusion: The observational study showed that standardized long-term recording can be performed in high-quality during acute COPD exacerbation as it does not require the patient’s cooperation. The good-quality data of coughs and wheezing were analyzed qualitatively and quantitatively. The long-term presentation of respiratory symptoms during an AECOPD offers the opportunity to evaluate factors that influence exacerbations and therapeutic approaches.Keywords: COPD, wheezing, cough, long term monitoring of respiratory sounds, CAT, exacerbation